An Analysis of the Contribution of Fisheries to the Economic Development of Kerala - V., Geethalakshmi; Gopal, Nikita; V., Radhakrishnan Nair; G.R., Unnithan (Fishery Technology, 2025)
Fisheries has been a traditional enterprise in Kerala with a contribution of 1.95% to the NSDP during 2003-04. The state has built an impressive infrastructure both in fish and fish processing sector The sector provides employment to more than one million people either directly or indirectly. This article outlines the impact of fisheries on the development of economy of the state and suggests measures to achieve the targets to ensure a viable fisheries sector.